2017
DOI: 10.2147/oajsm.s127395
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on high-intensity interval exercise for health promotion in children and adolescents

Abstract: Physical activity lowers future cardiovascular disease (CVD) risk; however, few children and adolescents achieve the recommended minimum amount of daily activity. Accordingly, there is virtue in identifying the efficacy of small volumes of high-intensity exercise for health benefits in children and adolescents for the primary prevention of CVD risk. The purpose of this narrative review is to provide a novel overview of the available literature concerning high-intensity interval-exercise (HIIE) interventions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 87 publications
1
76
0
2
Order By: Relevance
“…Despite contrasting SIT and high intensity interval training (HIIT) study designs, a consistent finding between all investigations is an improvement in CRF levels (8,10,33,34,52). A recent review demonstrated that HIIT has the potential to improve CRF by 2.2 to 23% in healthy, overweight and obese children and adolescents (5). Supporting this, findings from a meta-analysis reported large improvements in CRF (unstandardized mean difference 2.6 ml.kg -1 •min -1 ; 95% confidence interval 1.8 to 3.3 ml.kg -1 •min -1 ; Cohen's d effect size 1.05) (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite contrasting SIT and high intensity interval training (HIIT) study designs, a consistent finding between all investigations is an improvement in CRF levels (8,10,33,34,52). A recent review demonstrated that HIIT has the potential to improve CRF by 2.2 to 23% in healthy, overweight and obese children and adolescents (5). Supporting this, findings from a meta-analysis reported large improvements in CRF (unstandardized mean difference 2.6 ml.kg -1 •min -1 ; 95% confidence interval 1.8 to 3.3 ml.kg -1 •min -1 ; Cohen's d effect size 1.05) (19).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence demonstrates the potential of HIIT to improve CMR outcomes in children and adolescents (5,30,33,40,48,52). A recent review on the effect of HIIT on CMR outcomes (5) concluded that school-based HIIT induces similar or superior benefits compared to continuous aerobic exercise across a range of outcomes including body composition, insulin and glucose homeostasis, blood lipids and blood pressure in healthy, overweight and obese children and adolescents. Supporting this, a further review concluded that school-based HIIT was effective in improving CMR in overweight and obese adolescents (33).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of exercise are broad and include both physical and psychosocial components. The physical benefits encompass improved cardiovascular and muscular fitness, bone health, cognitive function, sleep, and energy . In addition, exercise prevents obesity, diabetes, and liver disease .…”
Section: Benefits Of Exercisementioning
confidence: 99%
“…The physical benefits encompass improved cardiovascular and muscular fitness, bone health, cognitive function, sleep, and energy. [1][2][3][4] In addition, exercise prevents obesity, diabetes, and liver disease. 5,6 Sports participation also improves confidence, self-esteem, and sense of normalcy in children when they participate in activities with their peers.…”
Section: Benefits Of Exercisementioning
confidence: 99%
“…A gyermekpopulációban is helye lehet a HIIT-edzésnek. Bond és mtsai 39 tanulmányt tekintettek át a cardiometabolicus mutatók javítására szánt közleményekből [39]. (A legtöbb labdajáték, a fogócska interval jellegű terhelést kíván, kellő szervezéssel és motivációval HIIT.)…”
Section: Interval Edzés Egyéb Betegségek Eseténunclassified